Some Challenges and Opportunities in Reliability Engineering - Zio, Enrico (IEEE transactions on reliability, 2016)
Today's fast-pace evolving and digitalizing World is posing new challenges to reliability engineering. On the other hand, the continuous advancement of technical knowledge and the increasing capabilities of monitoring and computing offer opportunities for new developments in reliability engineering. In this paper, I reflect on some of these challenges and opportunities in research and application. The underlying perspective taken stands on the following: The belief that the knowledge, information, and data (KID) available for the modeling, computations, and analyses done in reliability engineering is substantially grown and continue to do so; The belief that the technical capabilities for reliability engineering have been significantly advanced; The recognition of the increased complexity of the systems, nowadays more and more made of heterogeneous, highly interconnected elements. In line with this perspective, opportunities and challenges for reliability engineering are discussed in relation to degradation modeling and integration of multistate and physics-based models therein, accelerated degradation testing, component-, system- and fleet-wide prognostics and health management in evolving environments. The paper is not a review, nor a state of the art work, but rather it offers a vision of reflection on reliability engineering, for consideration and discussion by the interested scientific community. It does not pretend to give the unique view, nor to be complete in the subject discussed and the related literature referenced to.